Reserva biológica do Atol das Rocas (Atlântico Sul) sob pressões de impactos humanos: subsídios para a conservação - Gurgel, Anne Larisse Alves Rebouças (2023)
Coral reefs are among the tropical marine ecosystems of greatest ecological and socioeconomic relevance due to their abundant biodiversity and numerous ecosystem services. Their characteristics in remote oceanic environments, such as atolls (circular or elliptical carbonate biogenic structures), have remarkable implications in the generation of marine hot spots where, from their high productivity, they enable the existence of a complex and rich trophic web, with a high degree of endemism. Currently, global climate changes (e.g. ocean acidification, increase in heat waves and sea level rise), and regional and local pressures (e.g. illegal fishing and marine debris) have caused severe impacts at spatial and temporal levels, making essential the development of research that seeks to understand the effects at cumulative level, even in isolated oceanic systems, considered as "pristine areas" and supposedly free of human impact. Thus, the objective of this dissertation is to discuss the effects of global, local and regional pressures on the fully protected conservation unit Atol das Rocas Biological Reserve (the only atoll in the South Atlantic). The results indicate that the region is being impacted by global pressures, especially with the more frequent, intense and longer lasting occurrence of marine heat waves in recent decades, as well as erosive processes in the biogenic structure in certain parts of the island. These factors promote strong risks to the coral community, causing a higher number and intensity of bleaching events; as well as to the fauna dependent on the islands emersed area, such as seabirds and turtles, vulnerable to the sea level rise. Despite having a reasonable effectiveness of management, the risk of introducing invasive alien species through the presence of marine debris is very high, given the vulnerability of the atoll's position to the influence of ocean currents coming from Africa. Another factor that intensifies this threat is connectivity, through a chain of seamounts, which makes the atoll susceptible to the same oceanic system of the Fernando de Noronha Archipelago, a destination with high tourist influx and where the presence of the lionfish Pterois spp. has already been recorded. With the diagnosis made here and new data from future research it will be possible to make more realistic projections of impacts due to multiple anthropogenic pressures.